Socio-economic Transformation through RKVY-RAFTAAR in Uttar Pradesh and Karnataka - Bhagya Vijayan,; Manjeet Singh Nain,; Rashmi Singh, N. V. Kumbhare, Ravi K. N., (Indian Journal of Extension Education, 2022)
Rashtriya Krishi Vikas Yojana- Remunerative Approaches for Agriculture and Allied Sector Rejuvenation (RKVY-RAFTAAR) is aimed at augmenting agricultural and allied sector income. A study was conducted to analyse the socio-economic changes generated by Rashtriya Krishi Vikas Yojana rechristened as Rashtriya Krishi Vikas Yojana- Remunerative Approaches for Agriculture and Allied Sector Rejuvenation (RKVY-RAFTAAR) in the states of Uttar Pradesh and Karnataka in 2022. 160 beneficiary farmers and 80 non-beneficiary farmers from both the states were personally interviewed to elicit the socio-economic changes generated by the programme. The socio-economic transformation was higher for beneficiary farmers regarding annual income, entrepreneurial opportunity, occupational status, crop diversification, material possession, and access to the programme than for non-beneficiary farmers of both the states. Comparative analysis of the socio-economic transformation of beneficiary farmers of Karnataka and Uttar Pradesh revealed significant changes in the socioeconomic indicators except for entrepreneurial opportunity, education, and access to RKVYRAFTAAR. The changes brought about by the programme, before and after its launch revealed a significantly higher socio-economic impact on beneficiary farmers.